Pengukuran Technology Acceptance Model (Tam) Dalam Penggunaan New E-Learning Universitas Ahmad Dahlan - Arum Buana; Utaminingsih Linarti (Universitas Negeri Padang, 2021)
Information and Communication Technology (ICT) growth triggers various educational institutions, especially universities, to use technology in their learning. The learning model with ICT is known as e-learning which is designed using a Learning Management System (LMS). Ahmad Dahlan University (UAD) has been using e-learning since 2009. Currently, an e-learning system is very much needed in the online learning process. The UAD e-learning development team developed a new e-learning system to overcome distance education during the pandemic. This study was carried out to measure TAM in the use of UAD's new e-learning. The factors used are based on previous research using two primary factors from TAM, namely perceived usefulness and perceived ease of use by adding other aspects (1) instructor characteristic, (2) habit, (3) computer self-efficacy, and (4) system quality. The number of samples was determined using the slovin method with the results of 86 people, and the technique of deciding respondents was using purposive sampling. The data processing method in this study was carried out using the SPSS 20 application. The analysis results showed that habit, computer self-efficacy, system quality, and perceived ease of use significantly correlated with perceived usefulness. In contrast, instructor characteristics had no significant relationship with perceived usefulness. The immense contribution of the influence of instructor characteristic and habit factors on perceived usefulness simultaneously is 45.8%, for computer self-efficacy and system quality factors on perceived ease of use are 41.3% and for perceived ease of use factors on perceived usefulness is other variables influence 33, 2% and the rest.